Influence of 16 years of fertilization and manuring on carbon sequestration and agronomic productivity of groundnut in vertisol of semi-arid tropics of Western India. Issue 1 (2nd January 2021) - Srinivasarao, Ch.; Kundu, Sumanta; Yashavanth, B. S.; Rakesh, S.; Akbari, K. N.; Sutaria, G. S.; Vora, V. D.; Hirpara, D. S.; Gopinath, K.A; Chary, G. R.; Prasad, J. V. N. S.; Bolan, N. S.; et al.
Abstract: Productivity of cropland soils, especially in arid and semi-arid tropics of India rigorously declined due to increasing losses of soil organic carbon (SOC) over the past decades. In the present study, we examined a 16-years long term experiment with continuous mono cropping rainfed groundnut ( Arachis hypogaea ) to quantify the influence of fertilization and manuring on yield sustainability and C sequestration potential on rainfed Vertisols of Western India. The treatments include, i) T1 = control; ii) T2 = 100% recommended dose of fertilizer [RDF-20:40:40 kg ha −1 of N:P2 O5 : K2 O]; iii) T3 = integrated nutrient management [INM- 50% RDF + compost 6 Mg ha −1 + biofertilizers (BF)]; iv) T4 = organic nutrient source [compost 6 Mg ha −1 + vermicompost (VC) 2 Mg ha −1 + castor neem cake (CNC) 250 kg ha −1 + BF + mulching]. Maximum mean groundnut pod yield (1.17 Mg ha −1 ) was recorded in T2 which was statistically similar to T4 (1.16 Mg ha −1 ). However, Mann-Kendall test for yield trend suggests the consistency in yield increase under T3 treatment during the last 16 years. The rate of pod yield enhancement was 27 kg ha −1 for every Mg increase in profile SOC stock. The mean SOC concentration (g kg −1 ) of 1-m soil depth increased from 4.0 to 5.6 (40%) in T4 over control and the mean SOC sequestration rate was 0.63 Mg C ha −1  yr −1 . A minimum of 1.22 Mg C ha −1  yr −1 input was needed to maintain SOC stock at its antecedent level (zero change). We conclude that combined use of chemical fertilizers along with locally available organic resources is essential for enhancing SOC storage while achieving sustainable crop productivity in semi-arid agro-ecosystem.